Environmental quality in sediments of Cadiz and Algeciras Bays based on a weight of evidence approach (southern Spanish coast) - Rosado Alcarría, D. (2016)
This research applies an integrated sediment quality assessment method using a weight of evidence approach to Cadiz and Algeciras Bays (southern Spain). The method is composed of several analyses (particle size profile, aqua regia extractable metals, acid labile metals, total organic carbon, toxicity bioassay with Photobacterium phosphoreum and macrobenthic community alteration). The proposed method provides a single result, the environmental degradation index (EDI). EDI defined samples as low degraded (outer areas of both bays) and moderately degraded (Inner Bay of Cadiz Bay, the surroundings of Algeciras port and the northern part of Algeciras Bay). These samples showed the highest concentration of aqua regia extractable metals, which exceeded effects range-low (ERL) for Zn (51176 mg/l), Cu (1154 mg/l), As (4.39.5 mg/l), Hg (0.170.28 mg/l), Ni (2382 mg/l), and. Cr (37134 mg/l). They also exceeded some quality criteria for total organic carbon (4.06.5%) and toxicity (120240 TU/g) and showed poor results for macrobenthic community.